1993
DOI: 10.1002/jcp.1041540204
|View full text |Cite
|
Sign up to set email alerts
|

Induction of glucose regulated proteins during growth of a murine tumor

Abstract: Chronic anoxia, glucose starvation, low pH, and numerous other conditions induce the glucose-regulated system of stress proteins (GRPs), whose principal members are observed at 78, 94, and 170 kDa. These stresses may be expected to occur during growth in untreated tumors. To examine the possibility that GRPs are correspondingly induced, we have examined the protein profiles of small (< 0.1 g), intermediate (0.2-0.8 g), and large (> 1.8 g) radiation-induced fibrosarcoma (RIF) tumors grown on C3H mice. One and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
24
0

Year Published

1994
1994
2006
2006

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 47 publications
(25 citation statements)
references
References 27 publications
1
24
0
Order By: Relevance
“…Furthermore, GRP94 has also been identified as a murine tumor rejection antigen, indicating that to some extent it can also reside on the cell surface [20]. It has been shown that large amount of GRPs proteins were synthesized during tumor growth, HSP90 protein, in this case, was repressed [13]. The possible explanation might be that GRPs proteins is likely to be triggered by abnormalities in protein processing or folding in the endoplasmic reticulum, which, in some cases, has been shown to be resulted from abnormal glycosylation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, GRP94 has also been identified as a murine tumor rejection antigen, indicating that to some extent it can also reside on the cell surface [20]. It has been shown that large amount of GRPs proteins were synthesized during tumor growth, HSP90 protein, in this case, was repressed [13]. The possible explanation might be that GRPs proteins is likely to be triggered by abnormalities in protein processing or folding in the endoplasmic reticulum, which, in some cases, has been shown to be resulted from abnormal glycosylation.…”
Section: Discussionmentioning
confidence: 99%
“…GRPs was also induced by various stresses to function as molecular chaperones [11], [12]. Enhanced expression of GRPs during the growth of cancer cells imply its close relationship with the cell growth [13]. However, few reports have studied the expression of Grps genes especially during the course of tumor growth and differentiation in comparison with those of HSPs.…”
Section: Introductionmentioning
confidence: 99%
“…Grp170 is a major stress protein/molecular chaperone resident in the endoplasmic reticulum (ER; refs. [14][15][16][17] that is induced by stress conditions such as hypoxia, ischemia, and interference in calcium homeostasis (18). Studies have shown that grp170 is associated with the folding/ processing of secretory proteins such as thyroglobulin and immunoglobulin chains (14,19), suggesting that it may be involved in protein/peptide import into the ER (20)(21)(22)(23).…”
Section: Introductionmentioning
confidence: 99%
“…These cells are refractory to numerous DNAtargeted agents that are active only on proliferating cells. In cultured cell lines, accumulation of cells in G 0 -G 1 phase of the cell cycle has been reproduced by cell exposure to several stressor agents, including glucosamine (41,42). In such an in vitro model of stress-induced G 0 -G 1 cell cycle arrest, tumor cells remain sensitive to BN80927, whereas CPT, SN38, and VP-16 are devoid of activity.…”
Section: Discussionmentioning
confidence: 99%